Scientific and community knowledge strategy for conservation of biological diversity in the lagunar system of Cartagena de Indias (REVISTA AMBIENTAL AGUA, AIRE Y SUELO, 2024)
The location of the city of Cartagena gives specific biophysical particularities, internally accessing connected lagoon systems and in some routes they tend to be enclosed by mangroves, forming a biodiverse system that crosses the city through the Crespo neighborhood, reaching the Manga neighborhood, crossing through the Marbella neighborhoods. , Cabrero, Historic Center, Pie de la Popa and Bazurto. The city is considered a biological corridor made up of six bodies of water, known as: Caño de Juan Angola, Laguna del Cabrero, Launa de Chambacú, Laguna de San Lázaro, Caño de Bazurto and Ciénaga de las Quintas. The participation of these communities did not allow us to know the perception of the existing biodiversity in their surroundings, to understand the negative or positive relationships that can affect the processes of tourism and conservation of the species. The objective of this research is to build a baseline of biodiversity information by applying scientific and community knowledge in the lagoon system of Cartagena de Indias. The research strategy was based on the tour of the lagoon system, in the company of researchers, local experts and the community in general. Initially, the information was studied on a scientific basis investigated in CARDIQUE, Public Environmental Establishment (EPA), universities at the national level and at local level, scientific articles, undergraduate and graduate theses, biological collections, web pages and red books, CITES lists, periodic bulletins, in order to generate a matrix of biological information for the study area and its surroundings. Subsequently, it relates to the community by applying collective learning that consists of investigating real knowledge about the biodiversity of the area through participatory action, understanding it as a set of fauna, flora and culture, oriented to the implementation of scientific tourism. As a conclusion, a database of biological diversity was generated, validated by researchers, local experts and inhabitants of the community, managing to identify 94 species among birds, fish, reptiles, mammals and mangroves present in the lagoon system of Cartagena de Indias, department of Bolívar.
Keywords: Scientific tourism; lagoon system; biological diversity; community participation